2018
DOI: 10.1002/jbmr.3463
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal Skeletal Deletion of Dickkopf-1 Increases Bone Formation and Bone Volume in Male and Female Mice, Despite Increased Sclerostin Expression

Abstract: The Wnt antagonist Dickkopf-1 (Dkk1) is a negative regulator of osteoblast function and bone mass. However, because of the lack of appropriate models, many aspects of its role in the regulation of postnatal bone turnover and its cellular source have remained unknown. In this study, we deleted Dkk1 postnatally and in different cell types using various Cre-drivers (Rosa26-ERT2-Cre, Osx-cre, Dmp1-Cre) and assessed to which extent cells of the osteoblastic lineage contribute to the effects of Dkk1 on bone turnover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
42
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 42 publications
(111 reference statements)
7
42
1
Order By: Relevance
“…This is in contrast to a previous study that showed that deficiency of Sost protected mice from GC‐mediated bone loss via inhibition of bone resorption and not as expected by increasing bone formation . Potentially, this discrepancy may be explained by the already increased serum levels of sclerostin in conditional Dkk1‐deficient mice …”
Section: Discussioncontrasting
confidence: 97%
See 4 more Smart Citations
“…This is in contrast to a previous study that showed that deficiency of Sost protected mice from GC‐mediated bone loss via inhibition of bone resorption and not as expected by increasing bone formation . Potentially, this discrepancy may be explained by the already increased serum levels of sclerostin in conditional Dkk1‐deficient mice …”
Section: Discussioncontrasting
confidence: 97%
“…D , E ). Consistent with earlier studies, we found that an osteoprogenitor‐specific deletion of Dkk1 led to a significant reduction of Dkk1 serum levels, confirming that these cells are the major contributors to the systemic amount of Dkk1 …”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations